Business Intelligence (BI) in firm performance: Role of big data analytics and blockchain technology - Mladen Pancić; Dražen Cućić; Hrvoje Serdarušić (Economies, 2023)
The analysis of the causes or drivers of the adoption of big data analytics and blockchain and their subsequent influence on firm performance has become a significant need as a direct result of the rapidly expanding popularity of business intelligence. The purpose of this research is to present a model that investigates the direct and indirect influence of business intelligence on firm performance through the mediating roles of the adoption of big data analytics and blockchain. The analysis is based on data collected from a representative sample of 387 employees from 12 Information technology (IT) firms operating in Croatia. The study investigates these connections using a structural equation modeling. The findings showed that business intelligence has a direct and significant influence on firm performance. In addition, business intelligence significantly and positively influenced the adoption of big data analytics and blockchain and, in turn, firm performance. Additionally, the adoption of big data analytics and blockchain technology signified and positively mediated the relationship between business intelligence and firm performance. Both the mediations were partial. Finally, the study also provides managerial implications, limitations and future directions.
Keywords: 330; business intelligence; big data analytics; blockchain; firm performance; structural equation modeling (SEM)